2019
DOI: 10.15446/rsap.v21n2.71638
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de las necesidades y uso de servicios de atención en salud mental en Colombia

Abstract: Objetivo Analizar la relación existente entre la necesidad de atención y el uso de los servicios de salud mental en ColombiaMetodología Se comparó la prevalencia de trastornos mentales según la Encuesta Nacional de Salud Mental (ENSM-2015) y el registro de pacientes atendidos con diagnóstico de trastorno mental o del comportamiento en el Sistema Integral de Información (SISPRO-2013) la cual contiene los registros individuales de prestación de servicios de salud (RIPS) de todas las personas que acudieron al sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(4 reference statements)
0
4
0
1
Order By: Relevance
“…Hence, there are many integrated barriers in the system as it could have limited care resources available, since the use of mental health care services in Colombia does not cover the totality of people with mental disorders [33]. Zamora-Rondón et al [35] conducted a study on the mental health system. The study identified several issues, including administrative, regulatory, and geographical gaps, as well as coordination problems and a low supply of health services.…”
Section: Health and Mental Health Care Models In Colombia Brazil And ...mentioning
confidence: 99%
“…Hence, there are many integrated barriers in the system as it could have limited care resources available, since the use of mental health care services in Colombia does not cover the totality of people with mental disorders [33]. Zamora-Rondón et al [35] conducted a study on the mental health system. The study identified several issues, including administrative, regulatory, and geographical gaps, as well as coordination problems and a low supply of health services.…”
Section: Health and Mental Health Care Models In Colombia Brazil And ...mentioning
confidence: 99%
“…15 studies were excluded due to the lack of description of mental health services (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62), two because of their focus on characterising mental health disorders (63,64), two were only recommendations and were not implemented (65,66), and 1 due to the type of publication…”
Section: Study Selectionmentioning
confidence: 99%
“…1 153 results were imported on Rayyan for the title and abstract screening, of which 32 studies were selected for a full-text review, applying the full inclusion and exclusion criteria. 15 studies were excluded due to the lack of description of mental health services [12,24,[42][43][44][45][46][47][48][49][50][51][52][53][54], two because of their focus on characterising mental health disorders [55,56], two were only recommendations and were not implemented [57,58], and 1 due to the type of publication [15]. In the end, 12 studies were selected for data extraction.…”
Section: Study Selectionmentioning
confidence: 99%